PENGEMBANGAN MODEL ARSITEKTUR ENTERPRISE SISTEM INFORMASI MENGGUNAKAN EAP PADA PERGURUAN TINGGI (STUDI KASUS DI UNIVERSITAS DEHASEN BENGKULU) - Reno Supardi (UNIVED Press, 2016)
The college is an enterprise engaged in the field of education. In the current era to support the major activities in universities is needed the support of information systems. Failures in the implementation of information systems in a college is often caused because no planning. Planning information system in ordinary universities embodied in the blueprint. Enterprise Architecture Planning (EAP) is a process of defining the architecture for the use of information in order to support the business and planning to implement the architecture. EAP can be used to create a technology blueprint in an enterprise.Keyword: EAP, Enterprise, Blueprint, College